2002
DOI: 10.1021/jp020555b
|View full text |Cite
|
Sign up to set email alerts
|

The Moment Equations of Chromatography for Monolithic Stationary Phases

Abstract: The solution in the Laplace domain of the system of equations of the general kinetic model of chromatography provides equations relating the first absolute moment and the second central moment of elution bands to the characteristics of the retention equilibrium and the mass transfer kinetics, respectively. For continuous porous rod (i.e., monolithic) columns, these moment equations have the same form as those for conventional columns packed with spherical particles of a suitable packing material. However, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…17,26,27 On the other hand, the moment equations have also been developed for different separation media having various structural characteristics, such as the full-porous cylindrical fibers (monolith) and the superficially porous particles. [29][30][31][32] Similar moment equations for the superficially porous particles were also developed in a different manner. 33,34 Equations (11) and (12) comprehensively indicate the moment equations of μ1 and μ2′ for chromatography using the various packing materials: [29][30][31][32] µ τ ε ε ε ε ε 1 2 1 1 1 1…”
Section: Moment Equationsmentioning
confidence: 99%
“…17,26,27 On the other hand, the moment equations have also been developed for different separation media having various structural characteristics, such as the full-porous cylindrical fibers (monolith) and the superficially porous particles. [29][30][31][32] Similar moment equations for the superficially porous particles were also developed in a different manner. 33,34 Equations (11) and (12) comprehensively indicate the moment equations of μ1 and μ2′ for chromatography using the various packing materials: [29][30][31][32] µ τ ε ε ε ε ε 1 2 1 1 1 1…”
Section: Moment Equationsmentioning
confidence: 99%
“…The moment analysis (MA) method is one of the strategies for extracting information about chemical equilibrium and mass transfer and reaction kinetics from the values of μ1 and μ2′ of the elution peaks. [8][9][10][11][12][13][14][15][16][17][18] In the field of CE, a moment equation for μ1 was proposed to determine the association and dissociation equilibrium constants of intermolecular interactions. 19 Other moment equations have also been developed for CE systems, in which all components in a capillary, i.e., solute, ligand, and solute-ligand complex, simultaneously migrate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [14], it has been shown that all the different analytical expressions for H Cm and H Cs used in the literature [15][16][17][18][19][20][21][22][23][24][25] can all be reduced to the same single expressions although they often appear very different and employ totally different symbols. Slightly adapting the nomenclature from that used in [14] and using a notation that is specific for the presently considered PAC case, these expressions can be written as:…”
Section: Introductionmentioning
confidence: 99%
“…Another poorly tested approximation is that the mass transfer in the mobile and stationary zone occur independently of each other and that their contribution to the observed plate height is therefore additive. In addition, yet another problem is that the mass transfer rate in the mobile zone still has to be estimated from semi-empirical correlations such as the Wilson-Geankoplis [26] or the penetration model [27] that have not been truly validated, not even for non-porous columns [28].…”
Section: Introductionmentioning
confidence: 99%